ANALISIS PERBEDAAN PERAN GOOD CORPORATE GOVERNANCE DAN KINERJA KEUANGAN PADA BANK KONVENSIONAL DAN BANK SYARIAH DI INDONESIA - Muhammad Fatkhur Yusuf; Junaidi Junaidi; Anik Malikah (Universitas Islam Malang, 2020)
ABSTRACTThe purpose of this study is to see the differences in the role of good corporate governance and financial performance in conventional banks and Islamic banks in Indonesia in the period 2015-2019. The research method used in this study is quantitative. This study uses non-probability sampling techniques, namely using judgment sampling or purposive sampling. The sample in this study obtained 6 conventional commercial banks and 6 Islamic commercial banks in Indonesia. The results of the paired sample t-test show that there are differences in Return on Asset for Conventional Commercial Banks and Return on Assets for Islamic Commercial Banks, there are differences in Return on Equity for Conventional Commercial Banks and Return on Equity for Islamic Commercial Banks, there are differences in Operating Expenses on Operating Income for Commercial Banks. Conventional and Operational Expenses on Operating Income for Islamic Commercial Banks, there are differences in the Board of Directors of Conventional Commercial Banks and Independent Commissioners for Islamic Commercial Banks, there are differences in the Audit Committee for Conventional Commercial Banks and the Audit Committee for Islamic Commercial Banks, and there are differences in the Board of Directors of Conventional Commercial Banks and Sharia Commercial Bank Board of Directors. Keywords: The Role of the Good Corporate Governance, Financial Performance, Conventional Banks and Sharia Banks